Impact of gynecological screening in Lynch syndrome carriers with an MSH2 mutation. (7th August 2012) - Stuckless, S; Green, J; Dawson, L; Barrett, B; Woods, MO; Dicks, E; Parfrey, PS
<x xml:space="preserve">Abstract</x> Lifetime risk of developing endometrial cancer in Lynch syndrome carriers is very high and females are also at an increased risk of developing ovarian cancer. The aim of the study was to determine the impact of gynecological screening in MSH2 mutation carriers. Gynecological cancer incidence and overall survival was compared in female mutation carriers who received gynecological screening (cases) and in matched controls. Controls were randomly selected from non‐screened mutation carriers who were alive and disease‐free at the age the case entered the screening program. Median age to diagnosis of gynecological cancer was 54 years in the screened group compared to 56 years in controls (p = 0.50). Stage I or II cancer was diagnosed in 92% of screened patients compared to 71% in the control group (p = 0.17). Two of three deaths in the screened group were the result of ovarian cancer. Mean survival in the screened group was 79 years compared to 69 years in the control group (p = 0.11), likely associated with concomitant colonoscopy screening. Gynecological screening did not result in earlier gynecologic cancer detection and despite screening two young women died from ovarian cancer suggesting that prophylactic hysterectomy with bilateral salpingo‐oophorectomy be considered in female mutation carriers who have completed childbearing.